PELAKSANAAN PEMBELAJARAN TEKS CERITA PENDEK DI KELAS VIII SMP NEGERI 2 LANGSA - Zuraida Zuraida; Armia Armia; Maya Safhida (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
This study aims to describe the implementation of short story text learning in grade VIII of SMP Negeri 2 Langsa. This research employs a qualitative approach with a descriptive method. The subjects of this study consisted of Indonesian language teachers and 29 students in class VIII/1. Data collection techniques were carried out through observation, interviews, and documentation. The focus of this study includes three main aspects, namely planning, implementation, and evaluation of short story text learning. The results of the study indicate that (1) the learning planning is categorized as good because the learning objectives, content, strategies, and assessments are in accordance with the ministry of education and culture regulations, although the relevance to the local context still needs to be improved; (2) the learning implementation is categorized as very good because the teacher carried out the learning activities in accordance with the teaching module, actively involved the students, and concluded the lesson with reflection and evaluation; and (3) the learning evaluation is categorized as good because the teacher conducted assessments of attitude, knowledge, and skills based on the rubric, although self-assessment and peer assessment were not yet implemented optimally. Overall, the implementation of short story text learning in grade VIII of SMP Negeri 2 Langsa was conducted effectively and positively contributed to the students’ literacy development.